TECHNOLOGY OPTIONS TO SUPPORT THE IMPLEMENTATION OF KNOWLEDGE MANAGEMENT - Harkat Christian Zamasi (Bina Nusantara University, 2011)
Company is more aware that knowledge management is one of the important factors because it gives competitive advantages for them. Knowledge is intellectual asset that is owned by individual or company. Knowledge becomes very useful if it is documented or stored, organized, shared to others and can be understood and applied. Knowledge Management System (KMS) is made to manage knowledge. KMS does identifying process, capturing, organizing and disseminating knowledge. Technology is one of three model of KM that supports the implementation of KM. This time there are various options of technology that support the KM implementation for companies. In this research, there are various options or types of technology that can be used to support the implementation of knowledge management.Keywords: Knowledge Management; Knowledge Management System; Technology Word